The Impact of Power Training on Muscle Power, Physical Performance, and Physical Functioning in Older Adults: A Descriptive Case Series - El Hadouchi M; Kiers H; Veenhof C; Van Dieën J (Clinical Interventions in Aging, 2025)
Mohamed El Hadouchi,1– 4 Henri Kiers,1,2 Cindy Veenhof,2,5 Jaap Van Dieën3 1Institute for Human Movement Studies, University of Applied Sciences Utrecht, Utrecht, the Netherlands; 2Research Group Innovation of Human Movement Care, University of Applied Sciences Utrecht, Utrecht, the Netherlands; 3Department of Human Movement Sciences, Vrije Universiteit Amsterdam, Amsterdam Movement Sciences, Amsterdam, the Netherlands; 4Health Research Consultancy, Sports & Science, Lochem, the Netherlands; 5Department of Rehabilitation, Physical Therapy Science and Sport, Brain Center, University Medical Center Utrecht, Utrecht, the NetherlandsCorrespondence: Mohamed El Hadouchi, Email Mohamed.elhadouchi@hu.nlPurpose: Powerful Ageing is a power training intervention offered by Dutch municipalities to improve the physical functioning of its older residents, thereby reducing their reliance on assistive living devices and social support services. This study aimed to investigate the effects of Powerful Ageing on muscle power, physical performance, and physical functioning in older adults immediately following the intervention and at 1-year follow-up.Patients and methods: The study design was a prospective longitudinal case series. Eligible older adults requesting social support services from their municipality participated in a 14-week power training intervention. Primary outcomes were categorized according to ICF health domains: within the function domain, muscle power was measured with a Power Squat Test and a Lifting Test; within the activities domain, physical performance was assessed using the Star Agility Run and Timed Up-and-Go Test; and within the participation domain, physical functioning was assessed using a patient-specific complaints questionnaire. Participant motivation, a secondary outcome, was assessed using a short questionnaire.Results: Participants showed statistically significant improvements performing the Power Squat Test (p< 0.001; effect sizes: 0.52– 1.00), the Lifting Test (p< 0.001; effect sizes: 0.64– 0.82), the Star Agility Run (p< 0.001; effect size: 0.61), and the Timed Up-and-Go Test (p< 0.001; effect size: 0.74) immediately following Powerful Ageing. Additionally, activities of daily life became significantly less difficult to perform (p-value < 0.001, effect sizes: 0.60– 0.78). Among participants who continued power training following the intervention, these improvements were even greater at 1-year follow up. Participant motivation was high throughout the duration of the study.Conclusion: Powerful Ageing led to significant improvements in muscle power, physical performance, and physical functioning in older adults. Among participants who continued power training in the year following the intervention, improvements progressed even further, suggesting long-term benefits. Further research is needed to confirm the sustainability of the effects of power training in older adults.Keywords: exercise intervention, elderly, power squat test, timed up-and-go test, motivation